Associations Between Children’s Numeracy Competencies, Mothers’ and Fathers’ Mathematical Beliefs, and Numeracy Activities at Home - Mues, Anna; Wirth, Astrid; Birtwistle, Efsun; Niklas, Frank (Frontiers in Psychology, 2022)
Children’s numeracy competencies are not only relevant for their academic achievement, but also later in life. The development of early numeracy competencies is influenced by children’s learning environment. Here, the home numeracy environment (HNE) and parent’s own beliefs about mathematics play an important role for children’s numeracy competencies. However, only a few studies explicitly tested these associations separately for mothers and fathers. In our study, we assessed mothers’ and fathers’ mathematical gender stereotypes, self-efficacy and their beliefs on the importance of mathematical activities at home, and tested their associations with parents’ numeracy activities and children’s numeracy competencies in a sample of N = 160 children (n = 80 girls) with an average age of M = 59.15 months (SD = 4.05). Both, fathers and mothers regarded boys as being more competent in mathematics than girls. If the study child was a girl, fathers showed less strong mathematical gender stereotypes favouring boys. Further, fathers when compared to mothers reported a greater mathematical self-efficacy. Mothers of girls with a higher compared to a lower mathematical self-efficacy believed girls to be more competent in mathematics and these mothers also reported more frequent numeracy activities at home. However, the non-invariant constructs and varying results lead to the question whether a revision of existing scales assessing parental beliefs and home numeracy activities is needed to investigate differences of mothers and fathers and their potential associations with children’s numeracy outcomes.